Christian-Muslim Relations. Volume 15 A Thematic History (600-1600) - Douglas, Pratt,; Tieszen, Charles L., (The History of Christian-Muslim Relations ;, 2020)
Christian-Muslim Relations, Volume 15, A Thematic History (600-1600) is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. The chapters within it illustrate the range, complexity, and dynamics of interaction between the two faiths during the first thousand years of encounter. All chapters primarily draw upon entries found in volumes 1-7 of Christian-Muslim Relations. They explore tropes of perception, image and judgement that each religious community held in respect to the other through these centuries, and discuss issues and topics that occupied Christians and Muslims in their interaction. The first millennium sets the scene for the modern era and our understandings of contemporary relations and issues. Contributors are Mark Beaumont, Clinton Bennett, David Bertaina, Ulisse Ceceni, David Bryan Cook, Martha Frederiks, Ayşe İçöz, Maha El Kaisy-Friemuth, Sandra Keating, James Harry Morris, Nicholas Morton, Gordon Nickel, Juan Pedro Monferrer-Sala, Tom Papademetriou, Gabriel Said Reynolds, Christian Sahner, Mark N. Swanson, Mourad Takawi, Luke Yarbrough.